The Student’s Reading Problems In Private School In Pematangsiantar - Limsardo Panjaitan; Nengsih P W Siahaan; Veronica A Tampubolon; Novyta Sipayung; Selviana Napitupulu (International Journal of Education and Humanities, 2022)
The aims of writing this paper is to explain the problems of students in reading and find the factors that influence high school students in reading English well. This study uses a qualitative descriptive method to describe in detail the students' difficulties in reading comprehension. To find out the results of the analysis that has been carried out and to describe the difficulties of students, the instruments that the researchers used in this study were observation, interviews, and documentation. The difficulties faced by students in reading are the number of difficult words, it is difficult to understand long words and sentences, they do not understand the main idea, they do not understand grammar, and it is difficult to conclude